Traditional Chinese Medicine in Neuroprotection after Brain Insults with Special Reference to Radioprotection. (26th November 2018) - Peng, Xiao Chun; Huang, Jiang Rong; Wang, Si Wei; Liu, Lian; Liu, Zhen Zhen; Sethi, Gautam; Ren, Bo Xu; Tang, Feng Ru
Abstract : With rapidly increased construction of nuclear power plants worldwide to reduce energy shortage and subsequent environment contamination, routine use of radiotherapy and radiodiagnosis equipment in the clinical medicine, the research on the health effect of radiation exposure has become a very important area to explore. Traditional Chinese Medicine (TCM) may be an ideal candidate therapy as it usually produces fewer side effects even with long-term administration. In this paper, we reviewed current therapeutic approaches to prevent radiation-induced brain neuropathological and functional changes. Neuroprotective effects of TCM in different brain injury models have been briefly summarized. We then reviewed the neuroprotective and radioprotective effect of TCM in different radiation exposure models and discussed the potential molecular mechanism(s) of the neuroprotective and radioprotective effect of TCM. The conclusions and future research directions were made in the last part of the paper.